2019
DOI: 10.1111/ijfs.14441
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterisation of antioxidant peptides from sweet potato protein by enzymatic hydrolysis with radio frequency pretreatment

Abstract: Effect of radio frequency (RF at 70, 80 and 90°C) pretreatment on production and characterisation of sweet potato protein hydrolysates (SPPH) prepared using Alcalase (ALC), Protease (PRO) and the combination of ALC + PRO was investigated. RF highly improved degree of hydrolysis (DH) and enhanced antioxidant activity of all SPPH produced by ALC, PRO and the combination as compared to traditional water bath (WB) heating pretreatment (P < 0.05). RF significantly increased molecular weight (MW) <3 kDa peptide frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Otherwise, an antioxidant hydrolysate was obtained from Douchi protein hydrolyzed by Alcalase under optimal conditions (63℃, 1.4% of enzyme / substrate, and 1.7 h) [220]. In another paper, peptides with OH scavenging activity of 74.52% at a concentration of 1.0 mg/mL were isolated from sweet potato protein hydrolysates prepared by Alcalase [221], and it has been reported that if the Alcalase hydrolysis was performed after high hydrostatic pressure [222] or temperature (at 70, 80 and 90 °C) pretreatment [223], the degree of hydrolysis and the antioxidant activity of peptides from sweet potato protein were improved.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Otherwise, an antioxidant hydrolysate was obtained from Douchi protein hydrolyzed by Alcalase under optimal conditions (63℃, 1.4% of enzyme / substrate, and 1.7 h) [220]. In another paper, peptides with OH scavenging activity of 74.52% at a concentration of 1.0 mg/mL were isolated from sweet potato protein hydrolysates prepared by Alcalase [221], and it has been reported that if the Alcalase hydrolysis was performed after high hydrostatic pressure [222] or temperature (at 70, 80 and 90 °C) pretreatment [223], the degree of hydrolysis and the antioxidant activity of peptides from sweet potato protein were improved.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Studies have shown that PEF does not destroy the stability of PAs, but affects the secondary structures (α-helix, β-turn and random coil) of peptides and reduces zeta potential [116,117]. In addition, radio frequency pretreatment, high-energy electron beam, and protease co-extrusion technology have also been shown to be beneficial for improving the enzymatic hydrolysis efficiency and activity of PAs [118][119][120].…”
Section: Sourcementioning
confidence: 99%
“…These peptides can have various physiological effects, such as antioxidant, antihypertensive, and anti‐inflammatory activities, making them of interest for functional food and nutraceutical applications. Research has demonstrated that RF treatment can effectively improve the hydrolysis of sweet potato proteins and significantly enhance the antioxidant activity of resulting hydrolysates (Zhang, Huang, et al., 2019b).…”
Section: Pretreatment Technologymentioning
confidence: 99%